ANALISIS SEGMENTASI PASAR WISATA KEBUN GOWA - Nur 'Iftitah; Andi Nixia Tenriawaru; Pipi Diansari (Hasanuddin University, 2020)
Market segmentation is the process of classifying heterogeneous whole markets into groups or segments that have similarities in terms of needs, desires, behavior and / or responses to specific marketing programs. Gowa Tourism Gardens is one of the tourist attractions in South Sulawesi which has a lot of tourism supporting facilities and is still in the development stage so market segmentation needs to be done. The purpose of this study is to identify the characteristics of visitors to the Gowa Tourism Gardens and analyze the dependencies between the Gowa Tourism Gardens market segmentation variables. This study determines the market segmentation by using consumer loyalty as the dependent variable and demographic, geographical, psychographic, and visitor behavior data as independent variables. The number of samples in this study as many as 150 people. Methods of data analysis using CHAID analysis. The results of this study indicate that most visitors to the Gowa Garden Tourism are women, adolescents, have a junior high school education, have student/ college student status, have an income ≤Rp500,000.00 per month, and from outside the region Gowa. The significant independent variable with the dependent variable of visitor loyalty based on the results of the CHAID analysis is the supporting facilities variable used by visitors to Gowa Garden Tourism and vehicle ownership. The significant independent variable with the dependent variable of visitor loyalty based on the results of the CHAID analysis is the supporting facilities variable used by visitors to Gowa Garden Tourism and vehicle ownership.